Association study between common variations in some candidate genes and prostate adenocarcinoma predisposition through multi-stage approach in Iranian population - Behnaz Beikzadeh; Seyed Abdolhamid Angaji; Maryam Abolhasani (BMC, 2020)
Abstract Background Prostate cancer is one of the five common cancers and has the second incidence rate and the third mortality rate in Iranian population. The purpose of this study was to evaluate the association of rs16901979, rs4242382 and rs1447295 on 8q24 locus, rs2735839 (KLK3 gene) and rs721048 (EHBP1 gene) with prostate adenocarcinoma through multi-stage approach to identify the polymorphisms associated with prostate cancer and use them as screening factors. Screening tests can identify people who may have a chance of developing the disease before detection and any symptoms. Methods The case-control study included 103 cases (prostate adenocarcinoma) and 100 controls (benign prostatic hyperplasia). Tetra-primer ARMS-PCR was used to genotyping of each participant. A Multi-stage approach was used for efficient genomic study. In this method, a smaller number of people can be used. Chi-squared, Fisher's exact test and logistic regression were used to investigate the SNPs associated with prostate cancer and Gleason score. Results In the first stage (59 men), the frequency of polymorphisms rs16901979, rs4242382, rs1447295, rs2735839 and rs721048 in the prostate adenocarcinoma group was evaluated compared to the control group (P-value < 0.3) in order to select meaningful polymorphisms. There was not any significant difference between genotype frequency rs16901979 (P = 0.671) and rs721048 (P = 0.474) in the case group compared to BPH. Therefore, these polymorphisms were eliminated, and in the second step (144 men), rs4242382, rs2735839 and rs1447295 were evaluated (P-value < 0.05). According to the total population (203 men), there was significant difference between genotype frequency rs4242382 (P = 0.001), rs2735839 (P = 0.000) and rs1447295 (P = 0.005) even after using Bonferroni correction (p = 0.016). The effect of these three polymorphisms on prostate cancer was not modified by age and PSA. There was a significant difference between the allelic frequency of A vs G (rs4242382, rs2735839) at all classes of Gleason score and A vs C (rs1447295) at Gleason score ≥ 8. Conclusions The results of this study for rs2735839, rs4242382 and rs1447295 indicate the association of these polymorphisms with prostate adenocarcinoma predisposition in Iranian population. Exposure effect is homogeneous between different ages and PSA level categories. These three polymorphisms should be studied in a larger population to confirm these results.